Observation of exotic 𝐽/𝜓⁢𝜙 resonant structure in diffractive processes in proton-proton collisions - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Glaser, Fabian; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; et al. (Physical review letters, 2025)
The first study of 𝐽/𝜓⁢𝜙 production in diffractive processes in proton-proton collisions is presented. The study is based on an LHCb dataset recorded at center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5 fb−1. The data disfavor a nonresonant 𝐽/𝜓⁢𝜙 production but are consistent with a resonant model including several resonant states observed previously only in 𝐵+→𝐽/𝜓⁢𝜙⁢𝐾+ decays. The 𝜒𝑐⁢0⁡(4500) state is observed with a significance over 6⁢𝜎 and the 𝜒𝑐⁢1⁡(4274) is confirmed with a significance of more than 4⁢𝜎.